Comparative Study of Topical Oxiconazole Cream (1%) Versus Ketoconazole Cream (2%) in the Treatment of Inguinocrural Dermatophytoses (Medicine Today, 2017)
A clinical trial was carried out for the duration of six months from September' 2012 to February' 2013 in the Department of Dermatology and Venereology, Shaheed Monsur Ali Medical College, Uttara Dhaka and patients attending private clinical chamber. To evaluate the effectiveness of oxiconazole cream in comparison to the ketoconazole cream for the treatment of inguinocrural dermatophytoses.A total number of 60 patients with inguinocrural dermatophytoses were included in the study of which 30 patients were treated with oxiconazole (Group A) and the rest 30 patients were treated with ketoconazole (Group B)once daily for 21 days and weekly the outcome of lesions were clinically evaluated and recorded.In group A, male and female were 17 (56.7%) cases and 13 (43.3%) cases respectively. In group B, male and female were 16 (53.3%) cases and 14 (46.7%) cases respectively.The mean age with SD in group A and group B were 28.93 ± 8.29 years and 31.36 ± 8.36 years respectively. The mean scoring with SD in group A and group B were 6.26 ± 2.22 minutes and 6.53 ± 1.81 minutes respectively at the time of observation and 4.23 ± 1.50 minutes and 5.13 ± 1.45 minutes respectively after 1 week and 2.00 ± 1.22 minutes and 3.25 ± 1.07 minutes respectively after 2 weeks. The difference between the mean score of the two group is significant (p=0.006). The mean scoring with SD in group A and group B were 0.00 ± 0.00 minutes and 1.75 ± 0.95 respectively after 3 weeks.Sotopical treatment oxiconazole has revealed itself to be as efficient as ketoconazole and it seems more effective and better tolerated than ketoconazole.Medicine Today 2016 Vol.28(2): 57-61